Statistics from space: Next-generation agricultural production Information for enhanced monitoring of food security in Mozambique - International Food Policy Research Institute (2023)
International Food Policy Research Institute (IFPRI). 2023. Statistics from space: Next-generation agricultural production Information for enhanced monitoring of food security in Mozambique. Component 1. Stakeholder engagement for impacts. PowerPoint presentation given during the Project Inception Workshop, VIP Grand Hotel, Maputo, Mozambique, April 20, 2023